Pengaruh Perlakuan Alkali terhadap Kekuatan Bending Komposit Berpenguat Serat Rami dengan Matrik Polyester - Totok Suwanda; Muhammad Budi Nur Rahman (Universitas Muhammadiyah Yogyakarta, 2010)
The objective of this study was to determine the influence of alkali treatment on the flexural strength and failure mode of jute fiber waste/polyester composite materials. The materials being used in this research werewaste of jute fibers, polyester resin, where as NaOH and aquades were utilised for alcali treatment. Prior to being embedded into polyester resin to produce composite boards employing press printing techniques (press mold), the fiber was alkalitreated for 0, 2, 4 and 6 hours by soaking into a 28% volume NaOH content solution. Flexural test was carried out in accorcance with the ASTM D790 standard, and macrographs of selected fracture surfaces of the specimens were capturedfor analysis in oerder to determine the characteristics of the fracture surfaces. Test results showed that the longer the alcali treatment time in the lower the flexural stress and strain, but the the higher the flexural modulus. The composite without alkali treatment reluted in 70.39 MPa bending stress, 1.85% bending failure strain, and 3.85 GPa bending modulus, whereas the 6 hours of alkali treatment resulted in 51.70 MPa bending stress, 1.27% bending failure strain, and 4.13 GPa bending modulus. Composite with alkali-treatmed fiberdid not exhibite any fiber pull out, and also experienced debonding due to shear forces can’t afford retained by the resin.